PERAN LPIA DALAM PENGEMBANGAN PROGRAM KEAGAMAAN DI PERGURUAN AL-AZHAR MEDAN - Ahmad Yamin Dalimunthe; Solihah Titin Sumanti (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2024)
This study aims to analyze religious programs developed by the Institute for the Development of Religious Sciences (LPIA), both in terms of the programs produced, their implementation, and the supporting and inhibiting factors faced. This study uses a descriptive approach to analyze the implementation of religious programs developed by LPIA. The results of the study indicate that LPIA plays an important role in the development of religious programs at Al-Azhar Medan College. This can be seen from the many religious programs that are developed and implemented well and systematically planned. These programs receive full support from the Foundation that manages Al-Azhar Medan College, and the obstacles that arise in the field are relatively minimal. LPIA also has an implementation team in each unit that makes it easier to run and supervise the implementation of the program. Each unit at Al-Azhar Medan College feels the benefits of the programs developed by LPIA, because the program functions as a means to instill spiritual values ​​in students, teachers, and employees in the environment of each school unit. With this religious program, it is hoped that it can form a better and stronger character in terms of faith and piety among the entire academic community of Al-Azhar Medan College.